Analisis saluran drainase Jalan Ahmad Yani Kabupaten Sragen menggunakan pemodelan EPA SWMM 5.2 - Bima Afrizal Yusuf Hanafi; Paska Wijayanti; Rasyiid Lathiif Amhudo (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
Jalan Ahmad Yani is a vital economic and accessibility corridor in Sragen Regency that frequently experiences functional disruptions due to waterlogging. Therefore, the urgency of this research lies in the pressing need to mitigate the risk of structural degradation of the road pavement and prevent economic losses caused by persistent regional logistical obstacles. The flooding on Ahmad Yani Street in Sragen Regency is disrupting traffic and community activities. This study aims to analyze design rainfall intensity (10 and 20-year return periods) and evaluate the capacity of the existing drainage system using EPA SWMM 5.2 simulation. Rainfall intensity calculations were performed using the Gumbel and Mononobe methods, with an ATM distribution. Simulation results showed peak rainfall intensity reaching 82.70 mm (10 years) and 92.70 mm (20 years). Drainage capacity analysis indicates critical points. Junction node J4 (DTA 1) consistently experiences overflow of 0.941 m³/s, despite the large capacity of conduit C3, indicating a significant upstream flow contribution. Junction J14 (DTA 2 Segment 1) shows a large overflow of up to 1.973 m³/s, as the limited capacity of conduit C11 is unable to accommodate the accumulated flow. Junction J36 (DTA 2 Segment 2) also consistently overflows at 1.017 m³/s, indicating that the upstream flow accumulation exceeds its capacity despite the large capacity of conduit C39. It is concluded that the existing drainage system on Ahmad Yani Street is unable to adequately drain the volume of water during peak rainfall intensity, causing flooding. Recommendations include increasing channel capacity at critical points and a thorough evaluation of the drainage network. By identifying hydraulic system failures using dynamic simulation, this research makes a significant contribution by providing a precise map of critical points and a technical model that can serve as a database for relevant authorities, particularly the Sragen Regency Government, in formulating more adaptive and sustainable urban drainage infrastructure rehabilitation and development.